Texts and studies on Russian universal grammar 1806 - 1812 Teil 2. The universal grammars of I. Rižskij, Char'kov 1806, N. Jazvickij, SPb. 1810. I. Timkovskij, Char'kov 1811. L.G. Jakob, SPb. 1812 - Biedermann, Johann; Freidhof, Gerd (Specimina philologiae Slavicae, 1984)
Slavic languages